Analisis Yuridis Eksploitasi Anak Melalui Media Sosial Tiktok : Perspektif Undang-Undang Perlindungan Anak - Hafiz Muharram Sk , Ahmad; Riza , Faisal (Dinasti Review Publisher, 2024)
Technological advances such as social media are indeed a source of problems if not utilized properly. Not infrequently there are people who use this to do exploitative things to children. Such is the case with an orphanage foundation allegedly exploiting children through TikTok accounts in order to get donations. The donations collected were used for the perpetrator's personal needs. Then the author is interested in discussing the case of child exploitation on TikTok social media by explaining several aspects of the legal regulation of child exploitation in Indonesia and the protection of children exploited through TikTok social media based on Law No.35 of 2014 concerning child protection. This research is normative juridical in nature, then this research adopts two main approaches: a statutory approach and a conceptual approach. And the results of this study explain that the concept of child exploitation on the TikTok social media platform is a criminal offense which is an offense as regulated in Law number 35 of 2014 concerning Child Protection. And for the perpetrators can be punished with a maximum imprisonment of 10 (ten) years and / or a maximum fine of Rp 200,000,000.00 (two hundred rupiah).